PENGARUH FREKUENSI BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA UIN SUSKA RIAU - Rawit Suci Mulia; Granita (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2025)
This study aims to determine the effect of learning frequency on academic achievement of students of the Mathematics Education Study Program Universitas Negri Sultan Syarif Kasim Riau. The research method used is quantitative with a simple linear regression approach. The sample in this study consisted of 31 students selected randomly, while data on learning frequency were collected using a questionnaire while academic achievement was measured through GPA. The results showed that learning frequency had a significant effect on student academic achievement (significance value 0.041> 0.05). This study is supported by the results of the questionnaire which showed the tendency of students to study independently in a fairly good duration and intensity. That learning frequency contributes to student academic achievement, although it does not fully determine it. This study provides a basis for developing learning strategies that can encourage consistent independent learning habits.